2019
DOI: 10.1007/s10518-019-00587-3
|View full text |Cite
|
Sign up to set email alerts
|

Local site effects estimation at Amatrice (Central Italy) through seismological methods

Abstract: We present the results of seismological and geophysical investigations performed by the "Istituto Nazionale di Geofisica e Vulcanologia" team operating in Amatrice village (Central Italy), in the emergency phases following the Mw 6.0 event of August 24th 2016, that caused severe damage in downtown and surrounding areas. Data from seven seismic stations equipped with both weak and strong motion sensors are analyzed in terms of standard spectral ratio to empirically define amplification function using a bedrock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…In particular, the authors found that a significant ground-motion amplification may have characterized the area of the old Pescara del Tronto settlement. Milana et al (2019) illustrate the results of seismological and geophysical investigations performed in Amatrice village, in the emergency phases following the Mw 6.0 event of August 24th 2016. Data from weak-and strong-motions and from ambient vibrations have been used to better understand the distribution of amplification factors in the investigated area.…”
mentioning
confidence: 99%
“…In particular, the authors found that a significant ground-motion amplification may have characterized the area of the old Pescara del Tronto settlement. Milana et al (2019) illustrate the results of seismological and geophysical investigations performed in Amatrice village, in the emergency phases following the Mw 6.0 event of August 24th 2016. Data from weak-and strong-motions and from ambient vibrations have been used to better understand the distribution of amplification factors in the investigated area.…”
mentioning
confidence: 99%
“…The 3A network (http://doi.org/10.13127 /SD/ku7Xm 12Yy9 ) was deployed by INGV, ENEA, and CNR, and operated from September 19, 2016 through half of November, 2016 Milana et al 2019). It was composed of 55 stations ("Appendix" and Map of the Municipalities (thin grey lines) involved in the MS3 studies, divided by territorial grouping (six coloured areas).…”
Section: A Temporary Network Of Accumoli-amatricementioning
confidence: 99%
“…The village was built on an alluvial terrace 60-80 m higher than the surrounding valley (Amatrice basin) and elongated in NW-SE direction with a length of about 2000 m and a maximum width of about 600 m [25] (Figure 1). It is bounded both at NE and SW by two river valleys and bordered by a steep slope to the north and to the west, and by a gentler slope to the south.…”
Section: Introductionmentioning
confidence: 99%
“…The Amatrice basin is filled by about 60-m-thick Quaternary fluvial deposits, laying above the Messinian siliciclastic deposits of the Laga Formation, which play the role of seismic bedrock for the area [27,28]. They are made by conglomerates and sands alternations, few tens of meters thick, which can generate a seismic impedance contrast that, together with the topographic effects, is able to generate a strong amplification effect [25,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation